2011
DOI: 10.4103/0974-8490.81957
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative and phytochemical analyses of leaf extracts of ten Apocynaceae species

Abstract: Background:The anticancer properties of Apocynaceae species are well known in barks and roots but less so in leaves.Materials and Methods:In this study, leaf extracts of 10 Apocynaceae species were assessed for antiproliferative (APF) activities using the sulforhodamine B assay. Their extracts were also analyzed for total alkaloid content (TAC), total phenolic content (TPC), and radical scavenging activity (RSA) using the Dragendorff precipitation, Folin–Ciocalteu, and 1,1-diphenyl-2-picrylhydrazyl (DPPH) assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 26 publications
3
25
0
Order By: Relevance
“…Furthermore, it has been reported that crude aqueous and methanolic extracts of Vernonia guineensis (Asteraceae) tuber demonstrates relatively weaker activity against DU145 cells, whereas dichloromethane extract is more potent with lower IC50 values (Toyang et al, 2012). Likewise, Wong et al (2011b) stated that only DCM (dichloromethane : methanol) leaf extract of Catharanthus roseus showed activity against MCF-7 cells while hexane, methanol, DCM and dichloromethane extracts were all found to be cytostatic (anti-proliferative). Considering the results of our study and the mentioned studies above, it can be said that activities of A. orientalis extracts may be augmented using different solvents in the extraction process.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that crude aqueous and methanolic extracts of Vernonia guineensis (Asteraceae) tuber demonstrates relatively weaker activity against DU145 cells, whereas dichloromethane extract is more potent with lower IC50 values (Toyang et al, 2012). Likewise, Wong et al (2011b) stated that only DCM (dichloromethane : methanol) leaf extract of Catharanthus roseus showed activity against MCF-7 cells while hexane, methanol, DCM and dichloromethane extracts were all found to be cytostatic (anti-proliferative). Considering the results of our study and the mentioned studies above, it can be said that activities of A. orientalis extracts may be augmented using different solvents in the extraction process.…”
Section: Discussionmentioning
confidence: 99%
“…Bark and latex are used as diuretic and purgative. [12] The essential oil obtained from the flower is used as ingredient in cosmetics, candles, potpourri, massage oils and aromatherapy.…”
Section: Ethnobotanical Usesmentioning
confidence: 99%
“…[45] Allamanda cathartica, Cerbera odollam, Dyera costulata , and Kopsia fruticosa did not display any APF activity. Leaves were sequentially extracted with hexane (Hex), dichloromethane (DCM), and methanol (MeOH).…”
Section: Introductionmentioning
confidence: 99%